2017
DOI: 10.1074/jbc.m116.770511
|View full text |Cite
|
Sign up to set email alerts
|

Signaling adaptor ShcD suppresses extracellular signal-regulated kinase (Erk) phosphorylation distal to the Ret and Trk neurotrophic receptors

Abstract: Proteins of the Src homology and collagen (Shc) family are typically involved in signal transduction events involving Ras/MAPK and PI3K/Akt pathways. In the nervous system, they function proximal to the neurotrophic factors that regulate cell survival, differentiation, and neuron-specific characteristics. The least characterized homolog, ShcD, is robustly expressed in the developing and mature nervous system, but its contributions to neural cell circuitry are largely uncharted. We now report that ShcD binds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Furthermore, the confirmed enrolment of ShcD as a substrate for other receptors, such as TrkB [10] , could justify the ability of ShcD to activate the RAS/ERK pathway in SK-N-AS overexpressing the ShcD protein with no GDNF treatment. While this manuscript was in preparation a study by Wills and colleagues revealed that ShcD deactivates ERK and AKT signalling downstream of RET and TrkB, which certainly concurs with our finding [30] ; nevertheless, their data do not reveal the consequence of the inhibition.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the confirmed enrolment of ShcD as a substrate for other receptors, such as TrkB [10] , could justify the ability of ShcD to activate the RAS/ERK pathway in SK-N-AS overexpressing the ShcD protein with no GDNF treatment. While this manuscript was in preparation a study by Wills and colleagues revealed that ShcD deactivates ERK and AKT signalling downstream of RET and TrkB, which certainly concurs with our finding [30] ; nevertheless, their data do not reveal the consequence of the inhibition.…”
Section: Discussionsupporting
confidence: 89%
“…The emerging picture thus positions ShcD not as a passive scaffold recruited to a stimulated receptor, but as an active signalling regulator that influences EGFR in various cellular networks. Indeed, the noncanonical nature of ShcD has been reinforced by our recent discovery that the adaptor suppresses ERK1/2 phosphorylation distal to neurotrophic receptors (Wills et al, 2017). Although signalling output was not examined in the present work, it is tempting to speculate that the EGFR mislocalization we describe herein could similarly disconnect the receptor from canonical pathways.…”
Section: Discussionmentioning
confidence: 73%
“…Intriguingly, ShcD is expressed similarly to ShcA in the SVZ, though ShcD demonstrates additional localization to cells lining the lateral ventricle. In the olfactory system, ShcD is found in an overlapping pattern with ShcC in the main olfactory bulb, and uniquely in the OE and glomeruli, and it has a distinct function in suppressing Erk activation downstream of TrkB [32]. Given the established role of TrkB in migration [33] and differentiation [34] of NPCs, along with its high expression in OE-derived NPCs [35], it is tempting to speculate that ShcD could play a novel role in growth factor-mediated signaling in NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit anti-ShcD (1:1000) was generated against the unique CH2 region. Its specificity has been confirmed by preadsorption with the original antigen prior to immunohistochemistry [8, 13], by immunoblot against lysates prepared from cells expressing other Shc proteins [8], and by immunoblot on brain lysates prepared from ShcD knockout mice [32].…”
Section: Methodsmentioning
confidence: 99%